Systemic Functional Linguistics as a Basic Theory in Translating English Wordplays - Herawati, Agnes (Humaniora, 2010)
Wordplay are exploited in order to bring a communicatively significant confrontation of two or more linguistic structures. Translating wordplays in English text into Indonesian is difficult; on the one hand, translator has to recognize the use of wordplays in rendering a defined effect and the characteristics of translated text. This paper is designed to explore the importance of systemic functional linguistics (SFL) related to translating English wordplay into Indonesian, particularly the strategies of dealing with those wordplays and its application in solving problems effectively.SFL is most appropriately applicable to text analysis especially wordplay analysis because it is constructed for the sake of text analysis.